Impact of ammonia-water concentrations on solar absorption refrigeration performance - Mohammed El Amine Chikh; Mohammed Benramdane; Abdennour Aliane; Bilal Abdesselam (Renewable Energy and Sustainable Development, 2025)
Increased demand for summer comfort due to heat waves is driving the adoption of absorption refrigeration systems. These systems use free solar energy and environmentally friendly refrigerants, offering a sustainable solution despite their lower efficiency. This study investigates the effect of refrigerant ammoniac (NH₃) mass concentration on the performance parameters of a single-effect solar absorption refrigeration system using the NH3/H2O binary pair. A thermodynamic model is developed to evaluate the system’s coefficient of performance (COP) under varying generator temperatures, evaporator temperatures, and pressures. Results show that the COP increases significantly with NH₃ concentrations up to a threshold (23-25%), beyond which it stabilizes. Optimal performance is achieved at a generator temperature of 114°C, a low pressure of 1 bar, and an NH₃ concentration of 25%, yielding a maximum COP of 1.296. Additionally, the COP decreases with higher evaporator temperatures and pressures, highlighting the critical influence of thermodynamic parameters. This analysis underscores the importance of optimizing NH₃ concentrations and system operating conditions to maximize energy efficiency and facilitate sustainable cooling applications in solar-rich regions. Received on, 10 February 2025 Accepted on, 25 March 2025 Published on, 10 April 2025